UNDERGRADUATE STUDENTS’ ENGLISH PROFICIENCY TEST SCORE AND THEIR CUMULATIVE GRADE POINT AVERAGE - Desi Wijayanti Ma'rufah (Lexeme : Journal of Linguistics and Applied Linguistics, 2021)
English Proficiency Test (EPT) is popularly used in higher education as a requirement of graduation. However, in fact, some students have not passed the minimum score of the test whereas English language proficiency is important in English Department. Since the class mostly use English to deliver the course, the students’ proficiency need to be concerned. Previous research (David, 2014) suggests that English language proficiency can be a predictor of academic achievement. Thus, this study purposed to find out whether there is any significant positive correlation between English Proficiency Test (EPT) score and Cumulative Grade Point Average (CGPA). Pearson product moment correlation was conducted to compute 35 data of EPT score and CGPA. The results show that there is a significant positive correlation between EPT score and CGPA of English Department students in a university of Purwokerto. Thus, the students should concern to their language proficiency in order to get successful academic achievement.